Electroceutical Silk–Silver Gel to Eradicate Bacterial Infection. Issue 4 (24th February 2020) - Vieira, Daniela; Angel, Samuel; Honjol, Yazan; Gruenheid, Samantha; Gbureck, Uwe; Harvey, Edward; Merle, Geraldine
Abstract: With more than 50% of bacteria resistant to standard antibiotics, new strategies to treat bacterial infection and colonization are needed. Based on the concept of targeting the bacteria synergistically on various fronts, it is hypothesized that an electrical insult associated with antibacterial materials may be a highly effective means of killing bacteria. In this work, an injectable conductive gel based on silk fibroin (SF) and silver nanoparticles (Ag‐NPs) is synthesized, capable of coating a zone of injury, allowing the application of a low electrical current to decrease bacterial contamination. With a high conductivity of 1.5 S cm −1, SF/Ag‐NPs gels killed 80% of Escherichia coli in 1 min, no toxicity toward Chinese hamster ovary cells is observed. The mechanism of an electrical composite gel combined with electrical wound therapy is associated with silver ion (Ag + ) release, and reactive oxygen species (ROS) production. The findings in the present study show a similar Ag + release for treatment with gels and the combined effect, whereas ROS generation is 50% higher when a small electrical current is applied leading to a broad bactericidal effect. Abstract : What if simple bioresorbable materials can prevent infections, combat antibiotic resistance, and help heal infected wounds or cavities, just by using a gel free of antibiotics? Here, an injectable bioresorbable bactericide material that can coat the zone of injury is combined with low‐level electrical current to kill 80% of bacteria in 1 min.